Small Bowel Adenocarcinoma as the Cause of Gastrointestinal Bleeding in Celiac Disease: A Rare Malignancy in a Common Disease - Jaleh Fallah; Maxwell Eyram Afari; Alfredo C. Cordova; Adam J. Olszewski; Taro Minami (Case Reports in Oncological Medicine)
Introduction. Celiac disease is associated with an increased risk of small bowel malignancies, particularly lymphoma. Its association with small bowel carcinoma is less known. Case Description. We report a case of an 89-year-old woman with celiac disease who experienced recurrent episodes of gastrointestinal bleeding and was ultimately found to have adenocarcinoma of the small intestine. Discussion and Evaluation. Diagnosis of small bowel adenocarcinoma is often delayed because of the need for specialized modalities, which are often deferred in the inpatient setting. Although resection is the modality of choice for small bowel tumors, a majority is either locally advanced or metastatic at diagnosis, and even localized cancers have worse prognosis than stage-matched colorectal tumors. The role of adjuvant chemotherapy is uncertain, but it is often offered extrapolating data from other gastrointestinal cancers. Small bowel carcinomas occurring in the context of celiac disease appear to be associated with higher rates of microsatellite instability than sporadic tumors, although other specific genomic abnormalities and mechanisms of carcinogenesis in celiac disease remain unknown. Conclusion. Recurrent episodes of gastrointestinal bleeding in a patient with celiac disease should prompt an early evaluation of the small bowel to assure timely diagnosis of carcinoma at an early curable stage.